Cord Blood-Derived Hematopoietic Stem/Progenitor Cells: Current Challenges in Engraftment, Infection, and Ex Vivo Expansion - Katsuhiro Kita; Jong O. Lee; Celeste C. Finnerty; David N. Herndon (Stem Cells International)
Umbilical cord blood has served as an alternative to bone marrow for hematopoietic transplantation since the late 1980s. Numerous clinical studies have proven the efficacy of umbilical cord blood. Moreover, the possible immaturity of cells in umbilical cord blood gives more options to recipients with HLA mismatch and allows for the use of umbilical cord blood from unrelated donors. However, morbidity and mortality rates associated with hematopoietic malignancies still remain relatively high, even after cord blood transplantation. Infections and relapse are the major causes of death after cord blood transplantation in patients with hematopoietic diseases. Recently, new strategies have been introduced to improve these major problems. Establishing better protocols for simple isolation of primitive cells and ex vivo expansion will also be very important. In this short review, we discuss several recent promising findings related to the technical improvement of cord blood transplantation.